Conceptual Modeling in Web-based Hypermedia Engineering with Com HDM - Jantan, Azrul Hazri; Sumari, Putras; Sulaiman, Shahida (2008)
The coexistence of different complex features in web hypermedia applications such as information structures, navigation access mechanisms. and user interface interaction, raises new issues on the user-centered modeling approach paradigm. Thus, to provide a clear structured view of application domain, web designers must identify and clearly define complex processes existed in such applications.